Pengaruh Strategi Pembelajaran dan GAya Kognitif Terhadap HAsil Belajar IPA SD - DARMONO, Al (Fakultas Tarbiyah Institut Agama Islam Ngawi, 2025)
This study aims to determine the effect of learning strategies and cognitive styles on science learning outcomes for fifth graders in elementary schools. This study uses an experimental method with a quantitative approach. The population and sample use purposive sampling, which is divided into an experimental class and a control class. Data analysis uses two-way analysis of variance (ANOVA) followed by the Tukey test at a significance level of ά = 0.05. The findings in this study are: (1) SPD are higher than learning using SPE. (2) There is an interaction between learning strategies and cognitive styles on science learning outcomes. (3) The results of the Tukey test show that the science learning outcomes of students taught using SPD are higher than those using SPE. (4) The results of the Tukey test show that the science learning outcomes of students with a FI cognitive style are higher than those with a FD cognitive style. (5) The results of the Tukey test show that the science learning outcomes of students with a FI cognitive style who are taught using SPD are higher than those taught using SPE. (6) Tukey Test results show that the science learning outcomes of students with a FD cognitive style who are taught using an SPE are higher than those taught using an SPD.